KI-Einsatz durch Lernende im Erkenntnisgewinnungsprozess - ein Review - Fox, Marvin Lee; Peeters, Hendrik; Fechner, Sabine (GDCP Jahrestagung)
Keywords: Artificial intelligence; education; chemistry

How can students be supported by ChatGPT as a tutor in hands-on chemistry education? - Fox, Marvin Lee; Peeters, Hendrik; Fechner, Sabine (Conference of The European Science Education Research Association (ESERA))
Keywords: Artificial intelligence; education; chemistry

Prompting bei AR-gestütztem Experimentieren im Chemieunterricht - Peeters, Hendrik; Habig, Sebastian; Fechner, Sabine (Jahrestagung der Gesellschaft für Didaktik der Chemie und Physik e.V. (GDCP))

Virtual Reality trifft Künstliche Intelligenz. KI unterstützt bei virtueller Praktikumsvorbereitung - Peeters, Hendrik; Hansel, Jan-Luca; Graute, André; Fischer, Matthias; Weinberger, Christian; Neiske, Iris; Fechner, Sabine (Laborpraxis)

Influence de l'utilisation de la réalité augmentée lors des expériences chimiques sur la connexion des niveaux de représentation dans les explications des élèves - Peeters, Hendrik; Habig, Sebastian; Fechner, Sabine (Actes des XIIIe Rencontres scientifiques de l’ARDIST)

VirtuChemLab - Ein VR-Unterstützungsformat zur Vorbereitung auf das reale Chemielabor - Peeters, Hendrik; Graute, André; Hansel, Jan-Luca; Fischer, Matthias; Fechner, Sabine (Lehrkräftebildung in der digitalen Welt - Zukunftsorientierte Forschungs- und Praxisperspektiven)

Does augmented reality help to understand chemical phenomena during hands-on experiments?–Implications for cognitive load and learning - Peeters, Hendrik; Habig, Sebastian; Fechner, Sabine (Multimodal Technologies and Interaction)
Chemical phenomena are only observable on a macroscopic level, whereas they are explained by entities on a non-visible level. Students often demonstrate limited ability to link these different levels. Augmented reality (AR) offers the possibility to increase contiguity by embedding virtual models into hands-on experiments. Therefore, this paper presents a pre- and post-test study investigating how learning and cognitive load are influenced by AR during hands-on experiments. Three comparison groups (AR, animation and filmstrip), with a total of N = 104 German secondary school students, conducted and explained two hands-on experiments. Whereas the AR group was allowed to use an AR app showing virtual models of the processes on the submicroscopic level during the experiments, the two other groups were provided with the same dynamic or static models after experimenting. Results indicate no significant learning gain for the AR group in contrast to the two other groups. The perceived intrinsic cognitive load was higher for the AR group in both experiments as well as the extraneous load in the second experiment. It can be concluded that AR could not unleash its theoretically derived potential in the present study.
Keywords: augmented reality; chemistry education; models; experiment; cognitive load

Einbettung von Augmented Reality in den Experimentierprozess - Peeters, Hendrik; Habig, Sebastian; Fechner, Sabine (Unsicherheit als Element von naturwissenschaftsbezogenen Bildungsprozessen)
Keywords: augmented reality; modelle; digitale Medien

Augmented Reality als Experimentierhilfe bei Beobachtung und Deutung - Peeters, Hendrik; Habig, Sebastian; Fechner, Sabine (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch?)
Keywords: digitale Medien